اصلاحِ احوال کے لیےقرنِ اول کی مسلم خواتین کا کردار اور اس کی عصری تطبیق (Al-Qamar, 2020)
According to Islamic point of view every Muslim is a preacher and reformer. Prophet Muhammad (ﷺ) directed the Muslims to convey others even if they have a single verse or tradition of Islam. In this perspective many Muslim reformers always have been trying to renovate the condition of Muslim individuals and societies within their jurisdictions and capacities. Muslim women have also considerably been contributing in this regard. This paper presents the role of the first-century Muslim women from the referred perspective. It provides some important accounts and activities of the woman belonged to the mentioned era. It suggests that modern day Muslim women should follow the footsteps of the first century Muslim women for the reformation and renovation of the situations and conditions of relevant Muslim individuals and societies.
Keywords: First century Muslim women; efforts; reformation